Perception of Local People towards Youth’s Migration in Dhampus, Nepal - Bhattarai, Rudra Prasad; Nepal, Ratna Mani (KMC Research Journal, 2024)
Migration is a phenomenon that explicitly affects social, economic, and cultural landscapes of societies especially in developing countries. This study examined Dhampus, a suburban village in Kaski, Nepal, to explore the factors associated with youth migration. The research question was why youths migrate from Dhampus despite the region famous for domestic as well as international trekkers, hotels and restaurants, an entry point to the Annapurna Base Camp, and having the hybrid economy of agriculture, tourism and industries. This study employed exploratory research design to answer the research questions. Six in-depth interviews with key informants and two focus group discussions with local people including farmers, businessman, hoteliers, leaders of political parties. Thematic analysis of the data revealed six factors: declining agriculture, limited job opportunities, insufficient infrastructure for tourism planning, inadequate local development planning, social and economic inequality and waning trust in political institutions. Together, these factors drive young people toward urban areas and overseas. The finding of this study implies that an inclusive and sustainable rural development planning is necessary in Nepal. The plan should focus specific local contexts in order it to hold youth's in the villages. Foremost action is job creation accompanied by quality higher education centers. Appropriate infrastructure development seems an integral to the local resources mobilization and employment generation.